Design of Applications Raw Material Inventory Control Methods Economic Order Quantity In PT Gemah Ripah Loh Jinawi Industry - Prayitno, Eka Febryan; Wulandari, Sri Hariani Eko; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Gemah Ripah Loh Jinawi Industri (GRLJI) is a fertilizer industry company which produces two types of products; phosphate and dolomite. Thecompany has quite large business process in ordering the fertilizer products from customers, manufacturing raw materials until delivering the accomplishes products to the customer back. However, in raw manufacturing process still has disadvantage like there is no control in specific inventory of raw materials which could make disruption production process in financial losses. It relates to the raw materials’ and customers’ schedule order late to deliver.Raw materials quantity should be bought in certain period with minimumcost. Then, calculate the Safety Stock in order to determine the amount ofinventory security by comparing the use of raw materials and searching the value of deviation standard. After that, calculate Re-order Point (ROP) which used to determine the value point of re-ordering raw materials. It was need an application control of raw materials by counting the total minimum quantity and calculating of raw materials stock amount and procurement as a safe point in production process. Economic Order Quantity method (EOQ) used to provide the quantity of raw materials which should be purchased at certain period with minimum cost.Based on application trial result by using the data synopsis which knownby the company in limited period, it is about 1 month or 4 weeks. The Datashowed the EOQ value, the Safety Stock, and the ROP on each formautomatically. The application also could help the data processing and controlthe raw materials processing faster. It was made the raw material inventorycontrol process scheduled without interrupting the production process.Keywords: Economic Order Quantity, Inventory control, application, fertilizer,raw materials